2019
DOI: 10.1017/s0305000919000357
|View full text |Cite
|
Sign up to set email alerts
|

The root nominal stage: a case study of early Nungon verbs

Abstract: The ‘root infinitive’ phenomenon in child speech is known from major languages such as Dutch. In this case study, a child acquiring the Papuan language Nungon in a remote village setting in Papua New Guinea uses two different non-finite verb forms as predicates of main clauses (‘root’ contexts) between ages 2;3 and 3;3. The first root non-finite form is an apparent innovation of the child, unacceptable in adult-to-adult speech, which must be learned from a special auxiliary construction in child-directed speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 25 publications
(23 reference statements)
0
35
0
Order By: Relevance
“…Very occasionally the Ku Waru children in our sample use Medial verbs in independent clauses (that is, in an utterance that contains only one verb; not a clause chain). This is relevant to note in connection with discussions in the child language literature of an "optional infinitive stage" of language acquisition, in which infinitives function as predicates in independent clauses (Rizzi, 1994;Hoekstra and Hyams, 1998;Wexler, 2011;Grinstead et al, 2014;Sarvasy, 2019). Across the entire Ku Waru child corpus for this study, such independent Medial verbs account for only 0.59% of the number of children's verbs 17 .…”
Section: The Presence Vs Absence Of Medial Verb Markingmentioning
confidence: 80%
See 2 more Smart Citations
“…Very occasionally the Ku Waru children in our sample use Medial verbs in independent clauses (that is, in an utterance that contains only one verb; not a clause chain). This is relevant to note in connection with discussions in the child language literature of an "optional infinitive stage" of language acquisition, in which infinitives function as predicates in independent clauses (Rizzi, 1994;Hoekstra and Hyams, 1998;Wexler, 2011;Grinstead et al, 2014;Sarvasy, 2019). Across the entire Ku Waru child corpus for this study, such independent Medial verbs account for only 0.59% of the number of children's verbs 17 .…”
Section: The Presence Vs Absence Of Medial Verb Markingmentioning
confidence: 80%
“…The following analyses compare the children's production of Medial verbs with specific reference to whether or not they are suffixed. This is of interest, as the Ku Waru children's use of Medial/medial verbs differs sharply from that in Nungon, another Trans New Guinea language (Sarvasy, 2019). We will return to this shortly.…”
Section: The Presence Vs Absence Of Medial Verb Markingmentioning
confidence: 94%
See 1 more Smart Citation
“…While multi-speaker constructed clause chains are attested in conversation between adults and between adults and children in the Papuan language Nungon (Sarvasy, 2015(Sarvasy, , 2017, these are generally limited in length to two turns. With the exception of the special case of a parent prompting a child to repeat a clause chain, clause by clause, as in the Nungon child speech corpus (Sarvasy, 2019b), the vast majority of clause chains in Nungon conversation begin and end within a single turn by a single speaker. A typical Nungon clause chain is in (3); while this comes from a monolog narrative, its length and structure are well-attested in conversation as well.…”
Section: Introductionmentioning
confidence: 99%
“…A case study of Nungon verb acquisition (reported in Sarvasy, 2019b) showed that medial verbs consistently represent between 14 and 31% of all verb tokens in adult speech directed at one child, aged 2;1-3;3. By age 3;3, the child herself was producing medial verbs in similar proportions to her parents.…”
Section: Introductionmentioning
confidence: 99%